High Dynamics of Ciliate Community Revealed via Short-Term, High-Frequency Sampling in a Subtropical Estuarine Ecosystem - Gu, Bowei; Huang, Hungchia; Zhang, Yizhe; Li, Ran; Wang, Lei; Wang, Ying; Sun, Jia; Wang, Jianning; Zhang, Rui; Jiao, Nianzhi; Xu, Dapeng (Frontiers in Microbiology, 2022)
Ciliates are pivotal components of the marine microbial food web, exerting profound impacts on oceanic biogeochemical cycling. However, the temporal dynamics of ciliate assemblages on a short time scale in the highly fluctuating estuarine ecosystem remain largely unexplored. We studied changes in the ciliate community during a short time frame in the high salinity waters (>26) of a subtropical estuary. Ciliate abundance, biomass, size and oral diameter structure, and community composition fluctuated considerably and irregularly over a few days or even a few hours. Spearman correlations and the generalized linear model revealed that heterotrophic prokaryotes (HPs) and viral abundances drove the dynamics of ciliate abundance and biomass. The structural equation model further identified a major path from the high-fluorescence content virus (HFV) to HPs and then ciliates. Given the substantial correlation between salinity and HPs/HFV, we proposed that the response of HPs and HFV to salinity drives the dynamics of ciliate biomass. Additionally, the Mantel test showed that phytoplankton pigments such as Lutein and Neoxanthin, phosphate, and pigmented picoeukaryotes were key covariates of the ciliate community composition. This study demonstrated the highly changing patterns of ciliate assemblages and identified potential processes regulating ciliate biomass and community composition on short timescales in a subtropical, hydrographically complex estuary.